Competing risks models for the deterioration of highway pavement subject to hurricane events. Issue 6 (3rd June 2019) - Inkoom, Sylvester; Sobanjo, John O.
Abstract: Various methods have modeled failures due to hazard events using joint survival functions by assuming independent failure among the events. This paper evaluates the impact of two competing risks events: "natural" crack deterioration, and hurricane failure (Hurricane Categories 1, 2, and 3), on 6702 highway pavement sections using the nonparametric survival probability (Kaplan–Meier estimates) and the cumulative incidence function (CIF). The risks are compared using the Logrank Test (to indicate if the survival probabilities of the risks are significantly different) and the hazard ratio (ratio of hazard rates based on time to failure covariate). From the results, it was observed that the contribution of the Hurricane Category 3 as a competing risk was significantly higher and different from that of crack deterioration. For example, the hazard ratio of the Hurricane Category 3 was twice that of the crack deterioration for the inland urban interstates roadways. Also, the hazard ratio between hurricane category 3 and crack deterioration was about one hundred and sixty percent for rural interstates and slightly above one hundred percent for urban non-interstates and rural non-interstates. The hazard ratios and CIF plots showed that impact of hurricanes on coastal roadways is more significant compared to the inland segments.